Balanced Scorecard And Malaysian Small And Medium Enterprises (SMEs) - Sulaiman, Sharifuddin (2005)
Balanced scorecard (BSc) has been recognized as one of the most effective approach in managing company's performance. Its provides an enterprise view of an organization overall performance by integrating financial measures with other key performance indicators around customer satisfaction, internal business processes and organizational growth, learning and innovation.